PROSPECTS OF COOPERATION OF TATARSTAN UNIVERSITIES WITH THE ENTERPRISES OF REAL SECTOR OF ECONOMY - A. I. Bikchantayeva (Russian Journal of Economics and Law)
Objective: to determine the need for and prospects of further development of cooperation of higher educational institutions with the enterprises of real sector of the economy. Methods: the methods applied were scienti.c research at empirical and theoretical levels that allowed: 1) to identify the problem of insuf.cient provision of the national economic system with quali.ed human resources and to specify ways of solving it, 2) basing on the method of selecting information sources, to summarize the available experience of cooperation of Tatarstan universities with enterprises of various spheres of activity, 3) analyzing the collected information, to determine further actions for transforming the higher education system to focus it on the priorities of economic systems innovative development. Results: basing on the analysis of the proposed issues, a set of further measures was identi.ed aimed at strengthening of the integration between educational and economic systems, which include: the need for coordinated activities of the national universities and enterprises of the real economy sector, implemented in the form of the joint projects creation and implementation; active participation of universities in the innovative activities of business structures; enhanced involvement of the interested economic entities into the employment of higher educational institutions graduates. Scienti. c novelty: the article reveals the practical importance of cooperation between universities and enterprises of different branches and spheres of activity, and proposes to deepen this cooperation in the areas, which enhance updating of knowledge obtained in the educational process through their implementation in practical activity of graduates and students at the enterprises-partners. Practical value: the main provisions and conclusions of the article can be used in the development of concepts of perspective development of the teaching staff and the main directions of cooperation of national universities with enterprises of the real economy sector.